2016
DOI: 10.1159/000447266
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Potential Pharmacokinetic Interaction between Nebivolol and Bupropion in Healthy Volunteers

Abstract: Background/Aims: The study aimed at investigating the effects of multiple-dose bupropion (potent inhibitor of CYP2D6) on the pharmacokinetics (PKs) of single-dose nebivolol (CYP2D6 substrate) and to evaluate the clinical relevance of this potential drug interaction. Methods: This open-label, nonrandomized clinical study had a 2-period design: during period 1 (reference), a single dose of 5 mg nebivolol was administered, while during period 2 (test), 5 mg nebivolol + 300 mg bupropion were ingested concomitantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Potent inhibitors of the same metabolic pathway, like fluoxetine (12), paroxetine (22) and bupropion (29) had a marked influence upon nebivolol pharmacokinetics and were responsible for an approximately 6-fold to 7-fold increase in AUC 0-∞ . The association of the beta-blocker with bupropion and paroxetine also revealed a 4-fold and 5.7-fold increased exposure to 4-OH-nebivolol, the active hydroxylated metabolite (22,29). On the other hand, pretreatment with duloxetine, a moderate CYP2D6 enzymatic inhibitor, had an impact on nebivolol pharmacokinetics, similar with the one attributed to fluvoxamine in this study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Potent inhibitors of the same metabolic pathway, like fluoxetine (12), paroxetine (22) and bupropion (29) had a marked influence upon nebivolol pharmacokinetics and were responsible for an approximately 6-fold to 7-fold increase in AUC 0-∞ . The association of the beta-blocker with bupropion and paroxetine also revealed a 4-fold and 5.7-fold increased exposure to 4-OH-nebivolol, the active hydroxylated metabolite (22,29). On the other hand, pretreatment with duloxetine, a moderate CYP2D6 enzymatic inhibitor, had an impact on nebivolol pharmacokinetics, similar with the one attributed to fluvoxamine in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Several clinical trials investigated not only whether a drug interaction does exist between enzymatic inhibitors like cimetidine, duloxetine, paroxetine or bupropion and nebivolol, but also whether clinical consequences are associated with these potential drug interactions. Although it was revealed that the aforementioned drugs determined an increased exposure to nebivolol, these drug combinations did not lead to greater reductions of the pharmacodynamic parameters (BP and HR) measured at rest or during exercise (22,23,29,30). Additionally, no published case reports that describe side effects induced by nebivolol when coadministered with fluvoxamine were found in the medical literature.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical trials [37,38,39] have proved PK interactions for nebivolol, another cardioselective β-blocker in combination with antidepressants. Carvedilol and nebivolol are two third-generation beta-blockers of choice for heart failure [40], which still need to be studied due to their intensive utilization in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its principle, IMSM can readily accommodate drug‐drug interactions involving multiple species (enantiomers, metabolites of the inhibitor), because the inhibition potency reflects the action of all molecular species at the site of interaction. A few examples are shown in Table 1 1, 3, 4. Of note, the interactions with bupropion were published in 2016, but were predicted using the parameters published by our group in 2011 5…”
Section: Tablementioning
confidence: 99%